Diaphragmatic stimulator - Gomez E., J.; Villanueva, D. (Revista Mexicana de Ingenieria Biomedica, 1989)
A device is presented to electrically stimulate the diaphragm through the motor points of the phrenic nerve, through electrodes implanted in the neck.